Human cytomegalovirus pUL10 interacts with leukocytes and impairs TCR‐mediated T‐cell activation. Issue 9 (28th June 2016) - Bruno, Luca; Cortese, Mirko; Monda, Giuseppina; Gentile, Michela; Calò, Stefano; Schiavetti, Francesca; Zedda, Luisanna; Cattaneo, Elena; Piccioli, Diego; Schaefer, Mary; Notomista, Eugenio; Maione, Domenico; et al.
Abstract : Human cytomegalovirus (HCMV) is known to exert suppressive effects on the host immune system through expression of various viral genes, thus directly and indirectly affecting antiviral immunity of the infected individuals. We report here that HCMV UL10 encodes a protein (pUL10) with immunosuppressive properties. UL10 has been classified as a member of the HCMV RL11 gene family. Although pUL10 is known to be dispensable for viral replication in cultured cells, its amino‐acid sequence is well conserved among different HCMV isolates, suggesting that the protein has a crucial role in viral survival in the host environment. We show that pUL10 is cleaved from the cell surface of fibroblasts as well as epithelial cells and interacts with a cellular receptor ubiquitously expressed on the surface of human leukocytes, demonstrated by ex vivo cell‐based assays and flow cytometric analyses on both lymphoid cell lines and primary blood cells. Furthermore, preincubation of peripheral blood mononuclear cells with purified pUL10 ectodomain results in significantly impaired proliferation and substantially reduced pro‐inflammatory cytokine production, in particular in CD4 + T cells upon in vitro T‐cell stimulation. The inhibitory effect of pUL10 is also observed on antigen receptor‐mediated intracellular tyrosine phosphorylation in a T‐cell line. Based on these observations, we suggest that pUL10 is a newly identified immunomodulatory protein encoded by HCMV. Further elucidation of interactions between pUL10 and the host immune system during HCMV may contribute to finding ways towards new therapies for HCMV infection.